Impact of Adaptive Educational Game Applications on Improving Student Learning: Efforts to Introduce Nusantara Culture in Indonesia - Hernawan Sulistyanto; Djumadi Djumadi; Bambang Sumardjoko; Muhammad Izzul Haq; Gamal Abdul Nasir Zakaria; Sabar Narimo; Dyah Astuti; Muhammad Syahriandi Adhantoro; Devary Pradana Setyabudi; Yasir Sidiq; Naufal Ishartono (Universitas Muhammadiyah Surakarta, 2023)
This study aimed to introduce Nusantara culture based on educational games by adjusting students' learning styles. Culture as an ancestral heritage tradition needs to be preserved by introducing it to the younger gen-eration from an early age. However, the survey results found that less than 26% of student respondents un-derstood Nusantara culture well. Compared to previous research, the model of cultural introduction through adaptive educational games is more fun because it is adapted to the way students learn. This research was carried out using the Design-Based Research (DBR) method through 4 stages of the procedure. The feasibil-ity test and application effectiveness test were carried out on a group of students from several elementary schools in Indonesia, who were taken using a cluster random sampling technique. The results of media design and content validation obtained an average value of 0.76 and 0.82, which means that the media is declared valid. The feasibility test used the System Usability Scale (SUS) with an average value of 80% in the acceptable category. The results of the research obtained a description of the comparison of the final scores of the control class and the experimental class, which was 55 compared to 75. This study concluded that learning media for introducing Indonesian culture based on adaptive educational games had a positive impact by effectively increasing learning outcomes on students' understanding of Indonesian culture. Further development of this game application can be expanded in the application of animation in more depth.